IMRPOVING STUDENT’S LISTENING COMPREHENSION THROUGH KEYWORD STRATEGY - FERRI YONANTHA; NANDA KRISTIA SANTOSO; NAELLY SAFITRI (State University of Medan, 2021)
Listening as the primary skill in learning English plays very important role. This study investigates if Keyword strategy can improve students’ listening comprehension. The study involved 22 students of the second semester Islamic Law Department students at STAIN Sultan Abdurrahman taken by using cluster random sampling technique. The study was a pre-experimental research with one group pretest-posttest design. The research was carried out into three stages: pretest, treatments by using Keyword Strategy, and posttest. The score of pretest was 65.23 (Sufficient) and the posttest score was 77.27 (Good) which further analyzed with a paired simple T-test by using SPSS. The results show that the probability 0.00 < 0.05 indicating that there is a significant improvement on students’ listening comprehension after being taught by using Keyword Strategy.